Implementation of Web-based of E-Marketplace for UMKM at XYZ University - Devega, Mariza; Walhidayat, Walhidayat; Yuhelmi, Yuhelmi (Politeknik Ganesha Medan, 2022)
One of the private universities in Pekanbaru, which has nine postgraduate faculties and 10 faculties with 21 study programs. The number of the academic community is quite large, there is already a whats app group that facilitates the entire Academic Community in terms of transacting selling goods or services online. However, in practice it has not been fully effective, one of which is because there are no clear rules in trade ethics, for example, one person may only post a maximum of two products a day because if there are too many, it will overwrite other seller's product postings as well. This often happens, causing whats app groups are only dominated by one or two people who post all the products sold along with their customer testimonials. This of course can harm other sellers, it can also disturb the comfort of the group for both sellers and buyers. Therefore, to answer these problems, a market place is proposed specifically for the entire XYZ’s Academic Community. In addition to reviving UMKM at XYZ University, it is also a forum to make it easier for lecturers, employees and also students to make transactions that are comfortable and effective for both sellers and buyers. Furthermore, system development will be carried out both from adding features, android-based and matters related to user convenience in interacting with the system.